COACHES’ WORK EXPERIENCE AS AN INDICATOR OF MANAGEMENT ATTITUDES IN KARATE - Milan Nešić; Vidosav Lolić (Sport Mont, 2008)
Sports in general, which, self-understandably, implies karate as well, be longs to that aspect of social improvement which focuses on satisfying individual and group needs, but those of a country too. Karate does not yield any material value, but it creates certain values important for the whole society which can be materialsed by other processes. Just like any other field of work, recruiting particular management personnel in karate is significant for indicating and positioning those needs that compel them to work in this very field. Therefore, one is certain: among the most significant factors that provoke activity are motives and attitudes. In today’s karate in Vojvodina particular managerial roles have not been well defined yet. The concept and strategy of a karate club as a basic organisational unit in sport is primarily based on knowledge, interests and motivation of a karate coach. Hence, there is a different motivational structure among those who are in karate.